METAFUNCTION AND SOCIAL CONTEXT IN LOCAL LANGUAGES IN NORTH SUMATRA - Harianto II; Teguh Satria Amin; Zulfitri Zulfitri (Jurnal Scientia, 2020)
Language is a communication tool that has a function to create experiences in terms of sounds and symbols in constructing words. And in every region there are languages spoken by the community. Especially in the province of North Sumatra, Indonesia. This language has its own characteristics which of course are influenced by the culture and environment in the area as well as the local wisdom that surrounds it. This study aims to examine the metafunctions as well as the social context in regional languages in North Sumatra province. The research method used is descriptive qualitative with interview and observation techniques. The results of the research show that there is a metafunction in the regional language of North Sumatra which influences this side of the language. In addition, the social context has an important role in shaping the meaning and function of language. Social context includes cultural, social, and situational contexts. In the cultural context, the regional language of North Sumatra is used as a presentation of beliefs, values and ideology in society. In a social context, the regional language of North Sumatra is used to maintain the relationship between speaker and listener. In a situational context, the regional language of North Sumatra is used to convey messages or information effectively.